(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Women empowerment is a debatable subject. At earlier time they were getting equal status with men. But they had faced some difficulties during post-Vedic and epic ages. Many a time they were treated as slave. From early twenty century(national movement) their statuses have been changed slowly and gradually. In this regard, we my mentioned the name of the British people.